(3GdeHGOFs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3hEfi deG JCedJ GdJhHjN GdLejd Yf GdCTjGA cfJ cJHJ Edjc hLhGHkG YeG SCdJ hCf CVef ai Pdc HMSH eG jchf cJGHkG CcJHg CaUd ajg djKHJ Gdbhd ai GdeHGOF s
(3BNQgG (B:s
(3Hd fUd HeG dG JYJQVg GdTchc GdJUOjb HeG jSHb Edi Gdhge Cfg eTchc agj efgG hdG fWQMg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/13) s
Keywords: (3GdadSaI hGdefWbs